Efektivitas Media Game Card dalam Meningkatkan Pengetahuan dan Sikap Pemilihan Jajanan Sehat pada Remaja - Nadia Riskita Tri Wiradhika; Wildan Alfira Gusrianto; Choirul Anna Nur Afifah; Hamidah Aula Rusydiana (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Unhealthy snack consumption among adolescents is often associated with low nutritional knowledge. Interactive learning media such as game cards are considered effective in enhancing engagement and learning outcomes. This study aimed to evaluate the effectiveness of game card–based nutrition education in improving adolescents’ knowledge and attitudes toward healthy snack selection at SMPN 2 Gedangan. A quasi-experimental two-group pretest–posttest design was employed involving 74 students aged 13–15 years. Data were analyzed using the Wilcoxon test and N-gain analysis. The results showed that improvements in knowledge and attitudes were higher in the experimental group compared to the control group. Knowledge improvement reached borderline significance (p = 0.050), while attitudes improved significantly (p = 0.001). N-gain results indicated moderate effectiveness for knowledge (63%) and high effectiveness for attitudes (78.90%). These findings suggest that game card–based education is effective, particularly in improving adolescents’ attitudes toward healthy snack selection.